Identifying key determinants of poverty in Slovakia - Mojsejová, Alena (University of Pardubice, 2019)
The article deals with identifying key determinants of poverty in Slovakia. The two main goals of this article are to examine which factors have a significant effect on poverty and to determine the influence of relevant factors on poverty of Slovak households. A logistic regression model was used to quantify the impact of selected factors on the risk of the poverty and for probability modelling. We compared two models, using data from EU SILC 2013 and EU SILC 2016. Statistically significant differences are by the region and also by the degree of urbanization. We found that variables such as gender, age, household type, households' economic activity, marital status, education, health, and tenure status significantly affected the occurrence of poverty. According to contingency coefficients, the rate of poverty was at most influenced by the economic activity, on the other hand, the lowest rate was obtained for general health of the person at the head of the household. The obtained results are compared with the known researches in this field.
Keywords: EU SILC; European Union Statistics on Income and Living Conditions; Europe 2020; poverty; logistic regression; I32; R1; C31